Monetary Transmission : Are Emerging Market and Low Income Countries Different? - Bulir, Ales (IMF Working Papers; Working Paper ;, 2015)
We use two alternative representations of the yield curve to test the functioning of the interest rate transmission mechanism along the yield curve based on government paper in a sample of emerging market and low-income countries. We find a robust link from shortterm policy and interbank rates to longer-term bond yields. Two policy implications emerge. First, the presence of well-developed secondary financial markets does not seem to affect transmission of short term rates along the yield curve. Second, the strength of the transmission mechanism seems to be affected by the choice of the monetary regime: countries with a credible inflation targeting regime seem to have 'better behaved' yield curves than those with other monetary regimes.